A system of linear equations is shown:

-3x + y = K

2x + 3y = L

Which system has the same solution as the system shown?

A.) -9x + 3y = -3k

2x + 3y = 11

B.) 6x - 2y = -2K

2x + 3y = L

C.) -3x + y = K

3x + 4.5y = L

D.) -3x + y = K

-8x - 12y = L

-3x + y = K

2x + 3y = L

Which system has the same solution as the system shown?

A.) -9x + 3y = -3k

2x + 3y = 11

B.) 6x - 2y = -2K

2x + 3y = L

C.) -3x + y = K

3x + 4.5y = L

D.) -3x + y = K

-8x - 12y = L

You can do anything to an equation that you want. As long as you treat both sides equally, it is still an equivalent equation.

If you multiply the first original equation by -2 and leave the second original equation alone, you will have the same equations as in B.), which would have the same solution.

-3x + y = K → 6x - 2y = -2k {multiplied first equation by -2}

2x + 3y = L → 2x + 3y = L {second equation stays the same}

If you multiply the first original equation by -2 and leave the second original equation alone, you will have the same equations as in B.), which would have the same solution.

-3x + y = K → 6x - 2y = -2k {multiplied first equation by -2}

2x + 3y = L → 2x + 3y = L {second equation stays the same}

**B.) 6x - 2y = -2k**

2x + 3y = L

2x + 3y = L

*- Algebra House*